Nerdy Birdy - Reynolds, Aaron, 1970-; Davies, Matt, (Matthew Keiland Parry), 1966- (New York : Roaring Brook Press, 2015)
A picture book about a nerdy birdy who just wants to hang out with the cool birds.
"A Neal Porter book.".
Kirkus Starred, June 2015.
Booklist, July 2015.
Horn Book, April 2016.
2.9
K-3
Keywords: Birds -- Juvenile fiction; Friendship -- Juvenile fiction; Birds -- Fiction; Friendship -- Fiction; Birds -- Fiction; Friendship -- Fiction; Birds -- Fiction; Friendship -- Fiction